Family analysis of immunoglobulin classes and subclasses in children with autistic disorder - Spiroski, Mirko; Trajkovski, Vladimir; Trajkov, Dejan; Petlichkovski, Aleksandar; Efinska-Mladenovska, Olivija; Hristomanova, Slavica; Djulejic, Eli; Paneva, Meri; Bozhikov, Jadranka (My University, 2009)
Autistic disorder is a severe neurodevelopment disorder characterized by a triad of impairments in reciprocal social interaction, verbal and nonverbal communication, and a pattern of repetitive stereotyped activities, behaviours and interests. Th ere are strong lines of evidence to suggest that the immune system plays an important role in the pathogenesis of autistic disorder. Th e aim of this study was to analyze quantitative plasma concentration of immunoglobulin classes, and subclasses in autistic patients and their families. Th e investigation was performed retrospectively in 50 persons with autistic disorder in the Republic of Macedonia. Infantile autistic disorder was diagnosed by DSM-IV and ICD-10 criteria. Plasma immunoglobulin classes (IgM, IgA, and IgG) and subclasses (IgG1, IgG2, IgG3, and IgG4) were determined using Nephelometer Analyzer BN-100. Multiple comparisons for the IgA variable have shown statistically signifi cant diff erences between three pairs: male autistic from the fathers (p = 0,001), female autistic from the mothers (p = 0,008), as well as healthy sisters from the fathers (p = 0,011). Statistically signifi cant diff erences found between three groups regarding autistic disorder (person with autistic disorder, father/mother of a person with autistic disorder, and brother/sister) independent of sex belongs to IgA, IgG2, and IgG3 variables. Multiple comparisons for the IgA variable have shown statistically signifi cant diff erences between children with autistic disorder from the fathers and mothers (p < 0,001), and healthy brothers and sisters from the fathers and mothers (p < 0,001). Comparison between healthy children and children with autistic disorder from the same family should be tested for immunoglobulin classes and subclasses in order to avoid diff erences between generations.
Keywords: autistic disorder, immunoglobulin classes, immunoglobulin subclasses, family analysis